The influence of UV-irradiation on the poly(vinyl alcohol)/hyaluronic acid film properties. (11th February 2019) - Skopinska-Wisniewska, J.; Kozlowska, J.; Grabska, S.; Stachowiak, N.; Kaczmarek, B.; Sionkowska, A.
Abstract: The mixtures of hyaluronic acid and poly(vinyl alcohol) were prepared to obtain new bioartificial materials. HA easily degrades after injection to the human body, so, the mixtures of these polymers can lead to new bioartificial materials with modified degradation behavior. It was also tested whether UV-radiation could be used as a sterilizing agent for these blends. FTIR analysis showed that hydrogen and ester bonds are formed between HA and PVA. The values of surface free energy point out that the polar groups of polymers are involved in the creation of H-bonds. UV-irradiation caused slight changes in surface properties.